2018
DOI: 10.1080/17482631.2018.1435097
|View full text |Cite
|
Sign up to set email alerts
|

Leisure and health benefits among Korean adolescents with visual impairments

Abstract: Purpose: The purpose of the study was to explore health benefits through leisure engagement among Korean adolescents with visual impairments. Method: Using semi-structured interviews, a total of 14 adolescents with visual impairments participated in this study. Results: Two salient themes were captured as health benefits as a result of leisure engagement: psychological wellbeing and personal growth. Conclusions: The findings suggest that leisure provides a venue for the development of self-expression, leisure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Increasing evidence supports the positive effects deriving from the participation in regular physical activity to achieve psychophysical health with an overall improvement of QoL [4]. In particular, regular physical activity is the mainstay of chronic disease prevention and health maintenance in both people with and those without disabilities, and clear evidence exists of its psychophysical benefits in visually impaired people [511]. Despite the importance of an active lifestyle, only a minority of the population is currently meeting the recommended levels of regular physical activity to achieve health and QoL benefits [12].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence supports the positive effects deriving from the participation in regular physical activity to achieve psychophysical health with an overall improvement of QoL [4]. In particular, regular physical activity is the mainstay of chronic disease prevention and health maintenance in both people with and those without disabilities, and clear evidence exists of its psychophysical benefits in visually impaired people [511]. Despite the importance of an active lifestyle, only a minority of the population is currently meeting the recommended levels of regular physical activity to achieve health and QoL benefits [12].…”
Section: Introductionmentioning
confidence: 99%
“…Leisure time also plays an important role in the development of people's social and personal relationships (Iwasaki, 2017). When the results of the research conducted on the positive effects of leisure time activities on psychology are examined, it has been seen that motivation and needs are important for people to take action (Hayosh, 2017;Joseph & Southcott, 2019;Kim & Park, 2018;Merelas-Iglesias & Sánchez-Bello, 2019). Hence, the motivation obtained in leisure activities helps to determine the behavioral intentions of people (Iwasaki &Havitz, 2004).…”
Section: Extended English Summarymentioning
confidence: 99%
“…A recent investigation also highlighted the influence of gender on physical activity and regular engagement of people with disability, detecting lower levels in the female component ( 12 , 13 ). Sport practice, recreational or competitive, offers an enjoyable and healthy psychophysical and socioemotional growth opportunity to visually impaired people while counteracting disability-related onset of physical and mental disorders ( 14 , 15 ). Although research addressing these topics is still scarce and almost no exercise guidelines tailored to this target are available, it has been demonstrated that regular physical activity practice plays a key role not only in the structuring of sensorimotor skills but also in the development of personality, autonomy, body awareness, and self-esteem.…”
Section: Introductionmentioning
confidence: 99%